Analysis of the Influence of Risk Management And Profitability of Companies At Companies Listed on The Indonesia Stock Exchange Year 2014-2016 With Hedging Strategies As Mediating Variable - Farouq, Andi; Ratnawati, Tri; Priyawan, Sunu (Archives of Business Research, 2018)
The business world is increasingly advanced and supported by increasingly sophisticated technologies and information systems, brought the impact of increasingly intense competition among the businessmen. Even this will be increasingly tight competition after entering the era of liberalisation of world trade market, because besides is an opportunity for the company–company in Indonesia to enter the international market, it has also led to a flood of products and services from abroad to the domestic market. Therefore, to deal with the increasingly strict business competition, the management companies are expected to be able to work more efficiently and effectively. Any wisdom taken should be able to provide optimal results for the company so that the company is still able to compete with other companies. The hypothesis of the research is H1: Risk management strategy significantly to influential hedge on companies listed on the Indonesia stock exchange Years 2014-2016, H2: Influential profitability significantly to hedging strategies in companies listed on the Indonesia stock exchange Year 2014 – 2016, H3: influential hedge Strategy significantly to value the company at companies listed on the stock exchange The effect of Indonesia Years 2014-2016. The population in the research this is on the Indonesia stock exchange Year 2014 – 2016. Method of data processing is using SEM (Equational Structure Modeling) with AMOS version 18. The result of hypotheses shows of the variable risk management hedging strategy based on the indicators-charge indicators will show significant results with a value of CR 3,285. This value is greater than 1.96. Besides significance levels obtained 0.001 (p < 0.05). The results of the estimation of parameters of the variable profitability against hedging strategies based on the indicators-charge indicators will show significant results with a value of CR 6.633. This value is greater than 1.96. Besides significance levels obtained 0.000 (p < 0.05). The calculation result shows the value of the CR 0,383 and the significant value of 0,702 (p> 0.05). This means that the results of the hedging strategy is not a positive and significant effect against the value of the company.